Padenie Berlina . The Fall of Berlin - Chiaureli, Mikhail (Mosfilm, 1949)
Film about the Second World War. The story presents the vicissitudes of a soldier at the front and his sweetheart in a German forced labor camp, juxtaposed with sequences of Stalin and Hitler conducting the war. Stalin, wise, kind and, of course, a supreme military leader is hilarious, Hitler is a mere caricature. One of the 'classics' of Stalinist cinema.